Preparation and properties of vanillin-based polyurethane materials for body temperature self-healing - Fu, Mingfu; Hu, Jiangfeng; Zhang, Xiaochun; Wang, Chaozhang; Liu, Yang; Niu, Jianzhuang; Sun, Yinglu; Yao, Dengzun; Jing, Xianghai (Frontiers in Materials, 2024)
It is difficult to obtain sustainable and fast self-healing polyurethane materials with excellent mechanical properties at low-temperature. In this work, we prepared a series of bio-based polyurethane materials were synthesized with HMDI, Polytetramethylene ether glycol and a vanillin-based chain extender containing dynamic imine bonds. By adjusting the ratio of soft and hard segments, As the content of hard segments increased, the storage modulus and tensile strength of the material increased, the elongation at break decreased, and the heat resistance improved. The results showed that this advanced polyurethane displayed excellent mechanical and self-healing properties due to the presence of a large number of hard segment structures with dynamic imine bonds. Moreover, the tight arrangement of hydrogen bonds can promote the exchange of dynamic imine bonds and endow the material with body-temperature self-healing ability. It can recover to 98% of its original stress in 20 min at 36°C.